Mammary dysplasia. Use of Vitamins A, B6 and E Benign Breast Disease - Cotrina D., Manuel (2015)
We reviewed 366 consecutive cases of patients with benign mammary pathology, grouping them into four groups: breast pain, simple cysts, Adenosis (dysplasia) and fibrocystic breast disease. These patients as a single treatment women received the combination of Vitamin A, B6 and E ** for a period of two months. Overall response improvement in 81 percent of cases was obtained. The answer was zero at 19 percent. Analyzing the response is obtained by groups that the group responded to treatment was better mastodynia 96 percent. The response was less favorable in the group Fibrocystic 66 percent of cases.